Valorising Defatted Soy Flour into High-Moisture Textured Vegetable Protein by Single-Screw Cooking Extrusion - Domas Galih Patria; Cindytia Selvina Bernas; Annur Ahadi Abdillah; Dodyk Pranowo; Jenshinn Lin (Program Pascasarjana Universitas Sriwijaya, 2026)
Background: Conventional meat production is approaching ecological limits, motivating sustainable, circular-economy protein alternatives. Defatted soy flour (DSF), a low-value co-product of soybean oil extraction, is protein-dense, fibre-rich and abundant in Indonesia, yet its use in high-moisture textured vegetable protein (HM-TVP) is unexplored. Objective: To valorise DSF into HM-TVP by single-screw cooking extrusion and determine how substitution ratio and screw speed govern its functional, proximate, textural, colour, microstructural, isoflavone and sensory quality. Methods: Three DSF:pea-protein-isolate (PPI) ratios (0:70, 15:55, 30:40) and three screw speeds (30, 40, 50 rpm) were examined in a 3×3 factorial design (n=3) at the Food Pilot Plant, National Pingtung University of Science and Technology (NPUST), Pingtung, Taiwan. Water absorption/solubility indices, proximate composition, texture-profile analysis, HunterLab colour, SEM microstructure, RP-C18 HPLC isoflavones and hedonic scores were determined, and data were analysed by two-way ANOVA with Tukey HSD, effect sizes (η²), Pearson correlation and principal component analysis. Results: DSF substitution dominated most responses (partial η²=0.57–0.99, p<0.001). Raising DSF from 0 to 30% increased water absorption index (1.92→3.43 g/g), crude fibre (2.79→6.40%), hardness (25.7→56.9 N) and chewiness, and shifted the isoflavone profile toward higher glycoside (genistin up to 1741 µg/g) and bioavailable aglycone concentrations, while reducing crude protein (77.1→63.3%), crude fat (1.86→0.93%), lightness (L* 78.1→72.4) and springiness. Higher screw speed raised water-soluble index and soluble-fibre release but lowered hardness and browning. Crude protein of all extrudates (63–77%) far exceeded the ≥50% benchmark for texturised soy products, and the 15% DSF blend at 40 rpm (D15S40) achieved the highest overall acceptability (4.10/5). Conclusion: DSF can partially replace pea/soy protein isolates in sustainable, phytonutrient-enriched meat analogues at lower cost.